2003
DOI: 10.1099/vir.0.18952-0
|View full text |Cite
|
Sign up to set email alerts
|

Two novel spliced genes in human cytomegalovirus

Abstract: Two novel spliced genes (UL131A and UL128) flanking UL130 were predicted from sequence comparisons between human cytomegalovirus (HCMV) and its closest known relative, chimpanzee cytomegalovirus (CCMV), and the splicing patterns were confirmed by mRNA mapping experiments. Both genes were transcribed with late kinetics and shared a polyadenylation site. Comparisons with wild-type HCMV in infected human tissues showed that three of five isolates passaged in cell culture contained disruptions of UL128, one was fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
131
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(142 citation statements)
references
References 20 publications
9
131
1
Order By: Relevance
“…Sequencing studies of clinical material also suggested that this may be a polymorphic site (data not shown). Similar genomic variability has been observed in a homologous region in HCMV encoding a gene product with similarity to ␤-chemokines (17). The extended U83A now encoded a signal sequence comparable to that of U83B, with both start codons initiating at the same position, giving a similar predicted N terminus as shown by N-terminal sequencing (24).…”
Section: Expression Purification and Identification Of Native Hhv-6mentioning
confidence: 62%
See 2 more Smart Citations
“…Sequencing studies of clinical material also suggested that this may be a polymorphic site (data not shown). Similar genomic variability has been observed in a homologous region in HCMV encoding a gene product with similarity to ␤-chemokines (17). The extended U83A now encoded a signal sequence comparable to that of U83B, with both start codons initiating at the same position, giving a similar predicted N terminus as shown by N-terminal sequencing (24).…”
Section: Expression Purification and Identification Of Native Hhv-6mentioning
confidence: 62%
“…This now encodes a predicted signal sequence much less likely to be used as described previously (23). Similarly, in fibroblast-passaged HCMV strains, deletions interrupt expression of a ␤-chemokine, suggesting that these chemokines may be detrimental or not necessary for in vitro cultivation in some cell types (17,19). Interestingly, as described earlier, the ␤-chemokine genes in HCMV and HHV-6 are genomic positional homologs, and in HCMV, this locus is associated with endothelial and DC tropism as well as capacity to transfer to lymphocytes, although its receptor specificity has not been characterized (18,19).…”
Section: Comparisons With Other Viral Chemokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the epithelial/endothelial determinant locus (UL128-UL130-UL131A; hereafter UL128L) is especially susceptible to genetic alterations after only a few passages in cultured fibroblasts (Akter et al, 2003;Bradley et al, 2009;Cha et al, 1996;Cunningham et al, 2010;Hahn et al, 2004;Prichard et al, 2001;Ryckman et al, 2006Ryckman et al, , 2008Sinzger et al, 2008;Stanton et al, 2010). Proteins encoded by UL128L, together with glycoprotein H (gH) and L (gL), form a gH-anchored pentamer complex that mediates HCMV entry of EP and endothelial cells via receptor-dependent endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…The open reading frames (ORFs) of HCMV had been mapped on the genome by computer analysis and sequences compared between different HCMV strains and different CMV genomes (Chee et al, 1990;Rigoutsos et al, 2003;Dolan et al, 2004). To date, most HCMV genes have not been extensively characterized with respect to their expression patterns, although the coding potential and transcript structures of a few predicted genes had been identified by analysis of mRNA splicing, Northern blotting, identification of protein, and localization of the coding ORF (Jones and Muzithras, 1991;Adam et al, 1995;Wing and Huang, 1995;Atalay et al, 2002;Akter et al, 2003;Awasthi et al, 2004;Jenkins et al, 2004;Bego et al, 2005). Different transcripts expressed from a single piece of DNA sequence have been observed.…”
Section: Introductionmentioning
confidence: 99%